Kualitas Air Dan Kandungan Beberapa Logam Di Danau Unhas (Water Quality and Concentration of Metals in Lake Unhas) - Yaqin, Khusnul; Karim, Yusri; Fachruddin, Liestiaty (Jurnal Pengelolaan Perairan, 2018)
Study on several metals in Lake Hasanuddin University (Unhas) has been conducted as a basis of management of the lake as an aquaculture activity. This study was performed by sampling of water, sediment and biota, such as fish.  The results revealed that the average of temperature 32.72 oC has exceeded the threshold of the quality standard.  The average of dissolved oxygen, ammonia, pH were 5.8 mg/l, 0.016 mg/l, and 7.72 respectively.  Consentrations of nitrate and phosphate were 0.39 and 0.28 mg / l, respectively. Concentrations of mercury (Hg), cadmium (Cd) and cobalts (Co) were not detected in water coloumn.  Arsenic (As) was detected in level that still allowed by the threshold of the quality standard.  Concentrations of chromium (Cr) and plumbum (Pb) have exceeded the threshold of the quality standard.  In sediment, Hg and As were not detected, but Cr was detected in level that not exceed the the threshold of the quality standard.  Conccentrations of Cd, Co and Pb detected exceed the threshold of the quality standard.  Silver barb (Barbonymus gonionotus) that live in the lake has been contaminated by As, Cd and Pb. Keywords: Lake Unhas, metals, aquaculture, Silver barb.